Where Women Rebel: PATTERNS OF WOMEN'S PARTICIPATION IN ARMED REBEL GROUPS 1990–2008. Issue 1 (2nd January 2016) - Henshaw, Alexis Leanna
Abstract: While a significant literature on women's participation in armed rebel groups exists, much of this work is focused on individual cases or regional comparisons among movements. This has led to a lack of cross-national work on women in insurgencies, and a limited understanding of the extent to which women are engaged in civil conflict internationally. This article introduces new data on women's involvement in seventy-two insurgencies active since 1990, and assesses the validity of several assumptions about women and rebellion drawn from existing literature on women in conflict and on civil wars generally. I show that women are active in rebel groups much more often than current scholarship acknowledges. This involvement includes frequent service in combat and leadership roles, where male participants are often presumed to be the default. Finally, while forced recruitment tactics are frequently used to bring women into service, much of their participation appears to be voluntary in nature.